2000
DOI: 10.1074/jbc.275.10.7289
|View full text |Cite
|
Sign up to set email alerts
|

Insulin Inhibits the Activation of Transcription by a C-terminal Fragment of the Forkhead Transcription Factor FKHR

Abstract: The forkhead rhabdomyosarcoma transcription factor (FKHR) is a promising candidate to be the transcription factor that binds to the insulin response element of the insulin-like growth factor-binding protein-1 (IGF-BP-1) promoter and mediates insulin inhibition of IGF-BP-1 promoter activity. Cotransfection of mouse FKHR increased IGFBP-1 promoter activity 2-3-fold in H4IIE rat hepatoma cells; insulin inhibited FKHR-stimulated promoter activity ϳ70%. A C-terminal fragment of mouse FKHR (residues 208 -652) that c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
61
1

Year Published

2001
2001
2009
2009

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 64 publications
(67 citation statements)
references
References 61 publications
(62 reference statements)
5
61
1
Order By: Relevance
“…One of the hepatic actions of insulin, working via activation of the Akt kinase, is to Ser/Thr phosphorylate and inactivate forkhead transcription factor(s). Of particular importance for this discussion, forkhead rhabdomyosarcoma transcription factor (FKHR) is a major regulator of IGFBP-1 mRNA (20,42,50,53,54). Nonphosphorylated FKHR in the nucleus activates IGFBP-1 transcription.…”
Section: Discussionmentioning
confidence: 99%
“…One of the hepatic actions of insulin, working via activation of the Akt kinase, is to Ser/Thr phosphorylate and inactivate forkhead transcription factor(s). Of particular importance for this discussion, forkhead rhabdomyosarcoma transcription factor (FKHR) is a major regulator of IGFBP-1 mRNA (20,42,50,53,54). Nonphosphorylated FKHR in the nucleus activates IGFBP-1 transcription.…”
Section: Discussionmentioning
confidence: 99%
“…However, we have now shown that renal IGFBP1 is also increased in our model of type 2 diabetes mellitus, where circulating GH is decreased and hyperinsulinaemia has been described [26]. This potential contradiction may be explained by recently discovered pathways of insulin resistance involving the downregulation of the transcription factor FOXO1 [27], a known insulin-controlled positive regulator of IGFBP1 transcription [28]. Insulin inhibits FOXO1 activity by phosphorylating it via v-akt murine thymoma viral oncogene homologue 1 (AKT1), thus preventing its entrance into the nucleus.…”
Section: Discussionmentioning
confidence: 69%
“…The carboxyl domain of Foxo1, when fused to a heterologous Gal4 DNA-binding domain, can stimulate Gal4 promoter activity in an insulin-responsive manner (31). In contrast, the amino domain of Foxo1 (designated Foxo1-⌬256) has been shown to act as a dominant negative mutant to inhibit PEPCK and G-6-Pase expression in cultured cells (21).…”
mentioning
confidence: 99%
“…Using the IGFBP-1 promoter-directed expression system, the forkhead transcription factor Foxo1 (or FKHR) has been shown to play an important role in mediating insulin action and regulating target gene expression (13,14,19,21,22). In the absence of insulin, Foxo1 binds to IRE in target promoters and stimulates the promoter activity (1,13,31). In response to insulin, Foxo1 undergoes phosphatidylinositol (PI) 3-kinase-dependent phosphorylation and is excluded from the nucleus, resulting in inhibition of Foxo1-dependent transcription (2,5,6,13,22,27).…”
mentioning
confidence: 99%
See 1 more Smart Citation